Long-term variations of the sea level on the western coast of the Antarctic Peninsula - Maderich, V.; Terletska, К.; Brovchenko, І.; Pishniak, D. (Український антарктичний журнал, 2019)
The aim of the study is to analyze seasonal and interannual changes in sea level on the western coast of the Antarctic Peninsula. Objects of study are seasonal and interannual variability of sea level, air temperature, pressure at sea level, precipitation in the period 1960–2018 at the Faraday/Akademik Vernadsky station, which was considered as representative site for the Antarctic Peninsula.